Optical function of intraocular lenses in different opacification patterns: metrology analysis of 67 explants - Łabuz, Grzegorz; Yildirim, Timur Mert; Khoramnia, Ramin; Son, Hyeck Soo; Auffarth, Gerd U. (Journal of cataract and refractive surgery, 2021)
Purpose: - To determine how the type of opacification would have compromised the function of intraocular lenses (IOLs) prior to explantation using metrology. - Setting: - David J Apple Laboratory, Heidelberg, Germany. - Design: - Laboratory investigation. - Methods: - Of 67 explanted IOLs, 28 with homogeneous calcification, 21 with localized calcification, and 18 subluxated IOLs without calcification that served as controls were identified. The modulation transfer function (MTF) cutoff (0.43 at 100 lp/mm) was used to define decreased optical quality, following the manufacturers' guidelines for IOL testing. Light scattering was evaluated in vitro using a clinical device. - Results: - Only 1 control IOL demonstrated a decreased MTF compared with 4 and 15 in the homogeneous and localized groups, respectively. The MTF-derived metrics did not differ between the homogeneous and control IOLs (P = .99), but both showed better performance than those with localized opacification (P < .001). The median straylight parameter in the homogeneous pattern was 181.8 deg2/sr (108.5 to 244.1 deg2/sr), but in the localized group, it was less [69.8 (17.7 to 250.8) deg2/sr] (P = .02). Both opacification patterns yielded a significant straylight increase compared with the controls (P < .001). - Conclusions: - The study demonstrated that optical quality differed between the 2 types of opacification. The centrally localized pattern showed a significant MTF reduction, indicating a larger potential to affect patient visual acuity. Although localized calcification demonstrated lower straylight than that found in the homogeneous form, both conditions may cause severe glare phenomena.